Assessment of heavy metals and ecological risk of pangas (Pangasianodon hypophthalmus) and tilapia (Oreochromis niloticus) farms in Bangladesh - Keya, Rifat Azad; Hasan, Jahid; Akter, Ajmala; Roy, Anamika; Razzak, Mohammad Abdur; Shaha, Dinesh Chandra; Rahman, Zinia; Ahsan, Md Emranul (Annals of Bangladesh Agriculture, 2023)
An investigation was conducted to evaluate the contamination levels of heavy metals (As, Pb, Cd, Cr and Cu) in surface water and sediment of pangas (Pangasianodon hypophthalmus) and tilapia (Oreochromis niloticus) aquaculture farms in four regions (Mymensingh, Cumilla, Bogura, and Jashore) of Bangladesh. The ecological risk index (ERI) was determined to assess the water quality index. The water contained As concentrations of 3.60–11.14 µg/L; Pb of 1.73–3.83 µg/L; Cd of 1.26–23.12 µg/L; and Cu of 6.08–45.22 µg/L; whereas the sediments contained As concentrations of 2.84–4.57 mg/Kg; Pb of 8.32–16.07 mg/Kg; and Cd of 0.22–12 mg/Kg. Most locations had moderate to low levels of pollution, and the levels of contamination decreased from Cd to Pb to As to Cr. The declining sequence of potential ecological risk factors of toxic metals in sediment was Cd > Pb > As > Cr. Cd's potential ecological risk factor ranged from 2.84 to 21.58, making it one of the elements with the highest potential for ecological danger compared with other metals in this study. The Igeo values for the metals under study showed the following hierarchy Cr > As > Pb > Cd. As had a geo-accumulation index of -1.87 to 0.82, Pb, Cd -0.48 to -1.13, and Cr registered -1.28 to -2.45. Ponds in four different regions were found to be safe and suitable for fish culture, however, it was recommended that continuous monitoring of heavy metal concentrations in the aquaculture sector is necessary to mitigate the threat of contamination. Ann. Bangladesh Agric.27(2):105-117